Is There a Relationship between Voice Quality and Obstructive Sleep Apnea Severity and Cumulative Percentage of Time Spent at Saturations below Ninety Percent: Voice Analysis in Obstructive Sleep Apnea Patients - Serhat Yaslıkaya; Ayşegül Altıntop Geçkil; Zehra Birişik (Medicina, 2022)
Background and Objectives: Apnea hypopnea index is the most important criterion in determining the severity of obstructive sleep apnea (OSA), while the percentage of the total number of times which oxygen saturation is measured below 90% during polysomnography (CT90%) is important in determining the severity of hypoxemia. As hypoxemia increases, inflammation will also increase in OSA. Inflammation in the respiratory tract may affect phonation. We aimed to determine the effects of the degree of OSA and CT90% on phonation. Materials and Methods: The patients were between the ages of 18–60 years and were divided into four groups: normal, mild, moderate, and severe OSA. Patients were asked to say the vowels /α:/ and /i:/ for 5 s for voice recording. Maximum phonation time (MPT) was recorded. Using the Praat voice analysis program, Jitter%, Shimmer%, harmonics-to-noise ratio (HNR), and f0 values were obtained. Results: Seventy-two patients were included. Vowel sound /α:/; there was a significant difference for Jitter%, Shimmer%, and HNR measurements between the 1st and the 4th group (p < 0.001, p < 0.001, and p < 0.001, respectively) and a correlation between CT90% and Shimmer% and HNR values (p < 0.001 and p < 0.021, respectively). Vowel sound /i:/; there was a significant difference in f0 values between the 1st group and 2nd and 4th groups (p < 0.028 and p < 0.015, respectively), and for Jitter%, Shimmer%, and HNR measurements between the 1st and 4th group (p < 0.04, p < 0.000, and p < 0.000, respectively), and a correlation between CT90% and Shimmer% and HNR values (p < 0.016 and p < 0.003, respectively). The difference was significant in MPT between the 1st group and 3rd and 4th groups (p < 0.03 and p < 0.003, respectively). Conclusions: Glottic phonation can be affected, especially in patients whose AHI scores are ≥15. Voice quality can decrease as the degree of OSA increases. The increase in CT90% can be associated with the worsening of voice and can be used as a predictor in the evaluation of voice disorders in the future.